Isoform-specific and ubiquitination dependent recruitment of Tet1 to replicating heterochromatin modulates methylcytosine oxidation - Arroyo, María; Hastert, Florian D.; Zhadan, Andreas; Schelter, Florian; Zimbelmann, Susanne; Rausch, Cathia; Ludwig, Anne Kathrin; Carell, Thomas; Cardoso, Cristina (Nature Communications, 2022)
Oxidation of the epigenetic DNA mark 5-methylcytosine by Tet dioxygenases is an established route to diversify the epigenetic information, modulate gene expression and overall cellular (patho-)physiology. Here, we demonstrate that Tet1 and its short isoform Tet1s exhibit distinct nuclear localization during DNA replication resulting in aberrant cytosine modification levels in human and mouse cells. We show that Tet1 is tethered away from heterochromatin via its zinc finger domain, which is missing in Tet1s allowing its targeting to these regions. We find that Tet1s interacts with and is ubiquitinated by CRL4(VprBP). The ubiquitinated Tet1s is then recognized by Uhrf1 and recruited to late replicating heterochromatin. This leads to spreading of 5-methylcytosine oxidation to heterochromatin regions, LINE 1 activation and chromatin decondensation. In summary, we elucidate a dual regulation mechanism of Tet1, contributing to the understanding of how epigenetic information can be diversified by spatio-temporal directed Tet1 catalytic activity.
Gesehen am 26.10.2022